Solid‐Phase Peptide Macrocyclization and Multifunctionalization via Dipyrrin Construction. (6th August 2021) - Wu, Yue; Chau, Ho‐Fai; Thor, Waygen; Chan, Kaitlin Hao Yi; Ma, Xia; Chan, Wai‐Lun; Long, Nicholas J.; Wong, Ka‐Leung
Abstract: We introduce a new and highly efficient synthetic protocol towards multifunctional fluorescent cyclopeptides by solid‐phase peptide macrocyclization via dipyrrin construction, with full scope of proteinogenic amino acids and different ring sizes. Various bicyclic peptides can be created by dipyrrin‐based crosslinking and double dipyrrin‐ring formation. The embedded dipyrrin can be either transformed to fluorescent BODIPY and then utilized as cancer‐selective targeted protein imaging probe in vitro, or directly employed as a selective metal sensor in aqueous media. This work provides a valuable addition to the peptide macrocyclization toolbox, and a blueprint for the development of multifunctional dipyrrin linkers in cyclopeptides for a wide range of potential bioapplications. Abstract : A facile and highly efficient synthetic protocol towards multifunctional fluorescent cyclopeptides by solid‐phase peptide macrocyclization via dipyrrin staple construction is introduced, where the dipyrrin moiety serves as a novel multifunctional staple linker for targeted protein imaging and selective metal sensing.